Clinical InvestigationsComparative analysis of three functional predictive assays in lymphocytes of patients with breast and gynaecological cancer treated by radiotherapy - Padjas, Anna; Kedzierawski, Piotr; Florek, Agnieszka; Kukolowicz, Pawel; Kuszewski, Tomasz; Góźdz, Stanislaw; Lankoff, Anna; Wojcik, Andrzej; Lisowska, Halina (Journal of Contemporary Brachytherapy, 2012)
Purpose: There is a need to develop predictive tests that would allow identifying cancer patients with a high risk of developing side effects to radiotherapy. We compared the predictive value of three functional assays: the G 0 aberration assay, the G 2 aberration assay and the alkaline comet assay in lymphocytes of breast cancer and gynaecological cancer patients. Material and methods: Peripheral blood was collected from 35 patients with breast cancer and 34 patients with gynaecological cancer before the onset of therapy. Chromosomal aberrations were scored in lymphocytes irradiated in the G 0 or G 2 phase of the cell cycle. DNA repair kinetics was performed with the alkaline comet assay following irradiation of unstimulated lymphocytes. The results were compared with the severity of early and late side effects to radiotherapy. Results: No correlation was observed between the results of the assays and the severity of side effects. Moreover, each assay identified different patients as radiosensitive. Conclusions : There is no simple correlation between the in vitro sensitivity of lymphocytes and the risk of developing early and late side effects.